1948 LONDON OLYMPICS GAMES IN TURKISH PRESS - Selami Özsoy (ümit doğan üstün, 2017)
The 14th Olympic Games in London that could not be held in 1940 and 1944 due to the World War II became a milestone in the history of the Turkish sport with the success of the Turkish wrestlers. The London Olympics in which the Turkish national team got the sixth place among 59 countries by winning 12 medals had widespread media coverage in the Turkish press. The success of the Turkish wrestlers in the Olympics made a nation, which did not enter the war but was exceedingly affected both politically and economically and the face of which did not smile for years burst into joy. That Nasuh Akar won the gold medal in freestyle, Gazanfer Bilge, Celal Atik, and Yaşar Doğu, Greco-roman Mehmet Oktav and Ahmet Kireççi from Mersin won the gold medal in the Olympics was announced under the headlines of "we became world champion" on the front pages of the newspapers. The newspapers sent reporters to London to follow the Olympics and conveyed the developments day by day with photographs. The fixtures of the Turkish wrestlers that ended with a victory were narrated with minute details. Hürriyet newspaper, which sent a photojournalist to London, tripled its circulation with its publications on the Olympics. In this study, the news, commentaries, and photos related to the 1948 London Olympics in Akşam, Cumhuriyet, Hürriyet, Vatan, and Ulus newspapers are examined.